Odpowiedzi

2010-03-03T14:39:29+01:00
A)6(x-4)-2=6x-24-2=6x-26

b)2(x+1)-3(x-1)=2x+2-3x+3=-x+1

c)-3(y-2)+4(y+2)=-3y+6+4y+8=y+14

d)5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13

e)2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b

f)1/2(4x-4)-2x=2x-2-2x=-2

g)x(x-1)-3(x^-x)^=x²-x-3(x⁴-2x³+x²)=
=x²-x-3x⁴+3x³-3x²=-3x⁴+3x³-2x²-x

h)5a(a-3)-3a(a-5)=5a²-15a-3a²+15a=2a²

i)3x(x+1/3y)-2y(1/2x-1/2)=3x²+xy-xy+y=3x²+y
2010-03-03T14:39:51+01:00
A) 6(x-4)-2 =6x - 24 - 2= 6x-26
b)2(x+1)- 3(x-1)= 2x+2 - 3x +3 = -x +5
c)-3(y-2)+ 4(y+2)= -3y +6 + 4y + 8 = y +14
d) 5(x-y-1)- 4(x+2)= 5x - 5y -5 -4x -8 = x - 5y -13
e) 2(3a+b) - 2(a-b)= 6a+ 2b - 2a + 2b= 4a + 4b
f) 1/2 (4x-4) - 2x = 2x - 2 -2x = -2
g) x(x-1) - 3(x^- x) = x^ - x - 3x^ +3x = - 2x^ + 2x
h) 5a(a-3) - 3a(a-5) = 5a^ - 15a - 3a^ +15 a = 2a^
i) 3x(x+1/3 y) - 2y(1/2 x - 1/2)= 3x^ + xy - xy +y = 3x^ + y
2010-03-03T14:45:19+01:00
A)6(x-2)=6x-12
b)2(x+1)-3(x-1)=2x+2-3x+3=x+5
c)-3(y-2)+4(y+2)=-3y+6+4y+8=y+14
d)5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
e)2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
f)1/2(4x-4)-2x=2x-2-2x=-2
g)x(x-1)-3(x^-x)=x^-x-3x^+3x=2x^+2x
h)5a(a-3)-3a(a-5)=5a^-15a-3a^+15a=2a^
i)3x(x+1/3y)-2y(1/2x-1/2)=3x^+xy-xy+y=3x^+y